The lotus eaters [compact disc, unabridged] - Soli, Tatjana (Blackstone Audio, 2010)
On the hottest summer day of 1975, Saigon braces for an inevitable North Vietnamese invasion. As a result, Helen Adams, an American journalist, and her lover Linh are forced to flee the capital. However, past ghosts and acts of betrayal plunge their lives into chaos.